(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Background: Yoghurt is one of the most unique and a universal dairy product which is not only good in taste but it has many health benefits. It is easily digestible and has high nutritional value. Papaya fruits have a juicy taste rich in antioxidants and nutrients like (Carotene, Vitamin B, flavonoids, folate, pantothenic acids and minerals such as potassium and magnesium, the fruit is also a good source of fibre. Objective: The present study deals with the development, standardization and sensory evaluation of papaya fruit yogurt. Materials and Methods: Papaya fruit yoghurt was prepared by using a household processing technique by incorporating the same two types of yoghurts (with and without the use of guava pectin & skim milk powder). Standardization, nutritional evaluation and sensory evaluation were conducted for developed papaya fruit yoghurt using the Ranking test, nine-point hedonic test and composite scoring test. Results: Sensory evaluation results showed that all the samples of type 1 and type 2 yogurt were palatable. Developed product suggested of good in taste and it has high overall acceptability. But type 2 yogurt sample was found very good for overall acceptability. The shelf life of the product was three days. Conclusion: It can be concluded that papaya fruit yogurt type 2 was more acceptable with pleasant organoleptic properties. The product can be prepared by household technique. It gives higher nutritional benefits and improves the digestive system.